OPTIMALISASI PEMANFAATAN SISTEM REKAM MEDIS ELEKTRONIK UNTUK MENINGKATKAN EFEKTIVITAS KERJA (Studi Pada Klinik Utama “X”) - Vivi Rizki Hensmit; Purwadhi Purwadhi; Achmad Dheni Suwardhani (Bajang Institute, 2025)
Electronic Medical Records (EMR) allow for the digital management of patient information, replacing traditional paper-based methods. “X” Primary Clinic faces challenges in medical and administrative efficiency, particularly regarding service time, which is a common patient complaint. This study aims to optimize EMR utilization as a solution to enhance work effectiveness. A qualitative descriptive research approach with focused interviews was employed. The study population consists of employees at “X” Primary Clinic involved in EMR implementation. The purposive sampling technique was used, with 10 informants, including the branch manager, human resources and administration supervisor, general practitioners, nurses, administrative staff, radiographers, laboratory analysts, IT personnel, and medical record officers. Data were collected through observations, interviews, and document analysis. The findings reveal adequate technological infrastructure, although general practitioners still rely on paper-based records. Moreover, EMR training for staff is limited and lacks regular implementation, affecting their ability to fully utilize the system. While management has provided supportive facilities for EMR adoption, routine evaluations and monitoring need improvement. Government support in EMR regulations and oversight is significant; however, network access and training for healthcare facilities require further enhancement. This study concludes that optimizing EMR implementation can improve work effectiveness and healthcare service quality, necessitating regular evaluations, enhanced training programs, and stronger policy support from management and the government to maximize EMR's benefits for medical staff and patients at “X” Primary Clinic